Study and analysis of various inclination pathway electrode tool in electrical discharge drilling. (2021) - Manikandaprabu, P.; Kumar Thakur, Deepak; Sathish Kumar, M.; Sivanesh Prabhu, M.; Ramesh Kumar, A.
Abstract: The response characteristics of Electrical Discharge Drilling (EDD) such as Material Removal Rate (MRR), critical drill depth, aspect ratio, taper angle, corner radius, drill quality are dependent upon the electrode design, fabrication mode, input variables, elimination of debris from machining area and working conditions. The present study aims to improve the response characteristics by modifying the design of a hollow cylindrical electrode. The modification consists of new angular pathway in the electrode with various angles (60°, 63°, and 66°) along with linear pathways. The response characteristics improvement noticed the nature of the Material Removable Rate (MRR), aspect ratio, and critical drill depth with the profile of proposed electrode. The proposed electrode has effectively removed the debris from machining area at an inclined pathway angle of 66° and presented a significant improvement in the average machining taper angle and corner. The overall quality of drilling improved with the proposed electrode design.